2014
DOI: 10.1016/j.yfrne.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid effects of estrogens on behavior: Environmental modulation and molecular mechanisms

Abstract: Estradiol can modulate neural activity and behavior via both genomic and nongenomic mechanisms. Environmental cues have a major impact on the relative importance of these signaling pathways with significant consequences for behavior. First we consider how photoperiod modulates nongenomic estrogen signaling on behavior. Intriguingly, short days permit rapid effects of estrogens on aggression in both rodents and song sparrows. This highlights the importance of considering photoperiod as a variable in laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 143 publications
3
44
0
Order By: Relevance
“…Rapid estradiol signaling has also been reported to affect behaviors that differ greatly between males and females such as aggression, copulation, and learning (as reviewed by Laredo et al , 2014). While there has been extensive study of how these behaviors differ between males and females (Adkins-Regan & Leung, 2006, McCarthy et al , 2012, Rhen & Crews, 2000, Riebel et al , 2002), and while these behaviors have been linked to rapid estradiol signaling, few studies address how rapid estradiol signaling mechanisms might differ between males and females to mediate or modulate these behaviors.…”
Section: Sex Differences In Acute Effects Of Estrogens In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid estradiol signaling has also been reported to affect behaviors that differ greatly between males and females such as aggression, copulation, and learning (as reviewed by Laredo et al , 2014). While there has been extensive study of how these behaviors differ between males and females (Adkins-Regan & Leung, 2006, McCarthy et al , 2012, Rhen & Crews, 2000, Riebel et al , 2002), and while these behaviors have been linked to rapid estradiol signaling, few studies address how rapid estradiol signaling mechanisms might differ between males and females to mediate or modulate these behaviors.…”
Section: Sex Differences In Acute Effects Of Estrogens In the Brainmentioning
confidence: 99%
“…The same group also showed that this sex difference is due to aromatization of testosterone into estradiol early in development and masculinized females resembled males in pCREB induction from estradiol (Meitzen et al , 2012; also discussed in 2.2). Szego et al (2006) found female pCREB was sensitive to estradiol treatment but Grove-Strawser et al (2010) did not find these effects in males, suggesting that a sex difference emerges early on for the response of pCREB to estradiol (Meitzen et al , 2012, reviewed by Laredo et al , 2014). …”
Section: Egr-1 Signal Transduction Mechanisms and Sex Differencesmentioning
confidence: 99%
“…Nonclassical steroid actions are typically considered too fast to be accounted for by altered gene transcription/protein translation, since they can occur within seconds to minutes of elevated local steroid concentration. Steroids can therefore influence neuronal membrane excitability and cell signaling cascades via ‘nonclassical’ mechanisms (Laredo et al, 2014; Vasudevan and Pfaff, 2008; Woolley, 2007). The parallels here with neuromodulation are clear.…”
Section: Broadening the Scopementioning
confidence: 99%
“…Women are also more likely to experience chronic PTSD that persists for more than a year (4, 5, 7) and carry a greater burden of this illness on the healthcare infrastructure (1). While there is much debate about what factors contribute to these disparities –from sociocultural and environmental influences (8) to sexual dimorphisms in physiology – there is, surprisingly, very little known about the biological mechanisms that underlie sex differences in PTSD. The overreliance of male subjects in preclinical animal models and in clinical research has, thus far, limited our progress in understanding the nature of psychiatric illnesses that disproportionately affect women.…”
Section: Introductionmentioning
confidence: 99%